2016
DOI: 10.1016/j.foodpol.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

From food availability to nutritional capabilities: Advancing food security analysis

Abstract: This paper has a threefold objective. First, it provides a comprehensive review of different approaches to analysing food security. Second, it highlights the added value provided by the capability approach and the human development paradigm. Third, it proposes a methodology to assess food security through this approach. Our proposal entails three basic steps: (1) analysis of food entitlements; (2) analysis of nutritional capabilities and (3) analysis of the capability to be food secure. In this way, we can mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 24 publications
0
162
0
12
Order By: Relevance
“…This is reflected in the 21% increase of HDDS of households living in houses, compared to low-income households. Other studies indicate that an increase in household income increases a household's economic access to food [56].…”
Section: Household Income and Dietary Diversitymentioning
confidence: 99%
“…This is reflected in the 21% increase of HDDS of households living in houses, compared to low-income households. Other studies indicate that an increase in household income increases a household's economic access to food [56].…”
Section: Household Income and Dietary Diversitymentioning
confidence: 99%
“…This is in contrast with our findings since the households in our research were found in poverty situation and extreme poverty. This leads us to guess that the households suffer from food insecurity, based on the reason that it is a poverty subcategory; this is the lack of income necessary to buy necessary food to survive in the given conditions (Frayne and McCordic, 2015;Burchi and De Muro, 2016;Gautam and Andersen, 2016;Sonnino and Hanmer, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Burchi and De Muro [13] wrote "The way food security is theorised, measured and finally analyzed affects the typology of policies that will be adopted. " The CPS Food Security Supplement was designed to measure three food security domains: uncertainty, quality, and quantity [14,15].…”
Section: Measuring Food Securitymentioning
confidence: 99%
“…Burchi and De Muro [13] reviewed a number of food security measures and concluded a capability approach can improve measurements by accounting for more direct and indirect drivers. However, they concede including all factors requires an ability to access large amounts of information and can be improbable [13]. A capability approach assesses food entitlements (employment status, assets, skill sets, etc.…”
Section: Measuring Food Securitymentioning
confidence: 99%